Staphylococcus aureus Mevalonate Kinase: Isolation and Characterization of an Enzyme of the Isoprenoid Biosynthetic Pathway - Voynova, Natalya E. (American Society for Microbiology, 2004)
It has been proposed that isoprenoid biosynthesis in several gram-positive cocci depends on the mevalonate pathway for conversion of acetyl coenzyme A to isopentenyl diphosphate. Mevalonate kinase catalyzes a key reaction in this pathway. In this study the enzyme from Staphylococcus aureus was expressed in Escherichia coli, isolated in a highly purified form, and characterized. The overall amino acid sequence of this enzyme was very heterologous compared with the sequences of eukaryotic mevalonate kinases. Analysis by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and analytical gel filtration chromatography suggested that the native enzyme is a monomer with a molecular mass of approximately 33 kDa. The specific activity was 12 U/mg, and the pH optimum was 7.0 to 8.5. The apparent K(m) values for R,S-mevalonate and ATP were 41 and 339 μM, respectively. There was substantial substrate inhibition at millimolar levels of mevalonate. The sensitivity to feedback inhibition by farnesyl diphosphate and its sulfur-containing analog, farnesyl thiodiphosphate, was characterized. These compounds were competitive inhibitors with respect to ATP; the K(i) values were 46 and 45 μM for farnesyl diphosphate and its thio analog, respectively. Parallel measurements with heterologous eukaryotic mevalonate kinases indicated that S. aureus mevalonate kinase is much less sensitive to feedback inhibition (K(i) difference, 3 orders of magnitude) than the human enzyme. In contrast, both enzymes tightly bound trinitrophenyl-ATP, a fluorescent substrate analog, suggesting that there are similarities in structural features that are important for catalytic function.